Functional characterization of a new ORF βV1 encoded by radish leaf curl betasatellite - Gupta, Neha; Reddy, Kishorekumar; Gnanasekaran, Prabu; Zhai, Ying; Chakraborty, Supriya; Pappu, Hanu R. (Frontiers in Plant Science, 2022)
Whitefly-transmitted begomoviruses infect and damage a wide range of food, feed, and fiber crops worldwide. Some of these viruses are associated with betasatellite molecules that are known to enhance viral pathogenesis. In this study, we investigated the function of a novel βV1 protein encoded by radish leaf curl betasatellite (RaLCB) by overexpressing the protein using potato virus X (PVX)-based virus vector in Nicotiana benthamiana. βV1 protein induced lesions on leaves, suggestive of hypersensitive response (HR), indicating cell death. The HR reaction induced by βV1 protein was accompanied by an increased accumulation of reactive oxygen species (ROS), free radicals, and HR-related transcripts. Subcellular localization through confocal microscopy revealed that βV1 protein localizes to the plasma membrane. βV1 was also found to relocate into the nucleus and interact with replication enhancer protein (AC3). The current findings suggest that βV1 functions as a protein elicitor and might play a key role during pathogenesis.